2020
DOI: 10.1111/acv.12563
|View full text |Cite
|
Sign up to set email alerts
|

The small home ranges and large local ecological impacts of pet cats

Abstract: Domestic cats (Felis catus) are a conservation concern because they kill billions of native prey each year, but without spatial context the ecological importance of pets as predators remains uncertain. We worked with citizen scientists to track 925 pet cats from six countries, finding remarkably small home ranges (3.6 AE 5.6 ha). Only three cats ranged > 1 km 2 and we found no relationship between home range size and the presence of larger native predators (i.e. coyotes, Canis latrans). Most (75%) cats used pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 39 publications
7
73
0
Order By: Relevance
“…Not accounting for all the animals killed by cats is a critical bias in quantifying the totality of killing by domestic cat populations and their impact upon prey populations. 20,53 However, our study is of the effect of interventions on the relative frequency of prey returns and we do not extend our findings to the impact of killing upon prey populations. Hence our study conclusions are not subject to this bias.…”
Section: Prey Recording and Basis Of Response Variablesmentioning
confidence: 71%
See 1 more Smart Citation
“…Not accounting for all the animals killed by cats is a critical bias in quantifying the totality of killing by domestic cat populations and their impact upon prey populations. 20,53 However, our study is of the effect of interventions on the relative frequency of prey returns and we do not extend our findings to the impact of killing upon prey populations. Hence our study conclusions are not subject to this bias.…”
Section: Prey Recording and Basis Of Response Variablesmentioning
confidence: 71%
“…19 Such conditions in some residential areas mean that reduced individual predation rates may still result in considerable cumulative impacts. 20 Similarly, reductions in individual killing might not suffice to mitigate impacts upon particularly vulnerable populations or species.…”
Section: Open Accessmentioning
confidence: 99%
“…Study sites were considered to comprise a 100-m radius circle geographically centered at private homes (n = 48) or apartment complexes (n = 5) whose owner, tenant, or manager participated in the Neighborhood Nestwatch program (hereafter, NN), a community science program with 280 participants in the region (Evans et al, 2005). The study site area of 3.14 ha is consistent with estimates of cat home range size in residential areas (Haspel and Calhoon, 1989;Barratt, 1997;Schmidt et al, 2007a;Kays et al, 2019).…”
Section: Site Selectionmentioning
confidence: 99%
“…For example, Schmidt et al (2007a) reported survival among feral, semi-feral, and owned free-ranging cats to be 56, 90, and 100%, respectively, over a 14-month period -this corresponds to estimated survival rates of 87, 97, and 100% over our 3month study period. We could not account for the possibility of a cat leaving or arriving in the vicinity of a study site over the course of the study (see Kilgour et al, 2017); however, because cats frequently to maintain an established home range (e.g., Haspel and Calhoon, 1989;Barratt, 1997;Schmidt et al, 2007a;Kays et al, 2019), we judged this unlikely to meaningfully affect our final results. To avoid over-counting cats, individuals that could not be separated based on markings or physical characteristics were considered to be the same cat, even in ambiguous cases.…”
Section: Data Collectionmentioning
confidence: 99%
“…Population-level inference on space-use parameters is also importantboth for quantifying the area requirements of a typical organism and for quantifying the eect of covariates, such as species or taxa (Rehm et al, 2018;Habel et al, 2019;Matley et al, 2019;Poessel et al, 2020), sex (Morato et al, 2016;Naveda-Rodríguez et al, 2018;Desbiez et al, 2019;D'haen et al, 2019), body size (Naveda-Rodríguez et al, 2018;Ba²i¢ et al, 2019;Desbiez et al, 2019), age (Goldenberg et al, 2018;Averill-Murray et al, 2020;Kays et al, 2020;Mirski et al, 2020), movement characteristics (Swihart et al, 1988;Bowman et al, 2002;Desbiez et al, 2019), conspecic density (Trewhella et al, 1988;Erlinge et al, 1990;Massei et al, 1997), resource density (Massei et al, 1997;Herndal et al, 2005;Loveridge et al, 2009), habitat or biome (Morato et al, 2016;McBride and Thompson, 2019;Paolini et al, 2019;Tonra et al, 2019), human inuences (McBride and Thompson, 2019;Hansen et al, 2020;Rutt et al, 2020;Ullmann et al, 2020), weather (Kay et al, 2017;Matley et al, 2019;Mirski et al, 2020), and season or time (Goldenberg et al, 2018;Roer and Gregovich, 2018;…”
Section: Introductionmentioning
confidence: 99%